2019
DOI: 10.1002/acn3.50797
|View full text |Cite
|
Sign up to set email alerts
|

Mutation spectrum of Charcot‐Marie‐Tooth disease among the Han Chinese in Taiwan

Abstract: Objective Charcot‐Marie‐Tooth disease (CMT) is a clinically and genetically heterogeneous group of inherited neuropathies. Mutations in more than 90 genes have been implicated in CMT; however, the mutational spectrum of CMT in Chinese population remains obscure. This study aims to provide a comprehensive overview of the frequency of mutations in Taiwanese patients with CMT and look for genotype‐phenotype correlations. Methods Mutational analyses were performed on 427 unrelated Taiwanese patients with CMT by po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
36
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 43 publications
8
36
5
1
Order By: Relevance
“…These patients showed a milder disease course than patients with an early onset. These data are consistent with a Japanese study (50%) ( 8 ) and a study from Taipei (55.2%) ( 18 ), but the values higher than some Western countries (18–26%) ( 17 , 19 ), suggesting that Mongolian populations may have a mild phenotype due to genetic modifying factors ( 20 ) and or environmental factors and may be unaware of being affected. Some patients only had pes cavus, which did not warrant a detailed examination at hospitals, and hence, the prevalence may be underestimated.…”
Section: Discussionsupporting
confidence: 90%
“…These patients showed a milder disease course than patients with an early onset. These data are consistent with a Japanese study (50%) ( 8 ) and a study from Taipei (55.2%) ( 18 ), but the values higher than some Western countries (18–26%) ( 17 , 19 ), suggesting that Mongolian populations may have a mild phenotype due to genetic modifying factors ( 20 ) and or environmental factors and may be unaware of being affected. Some patients only had pes cavus, which did not warrant a detailed examination at hospitals, and hence, the prevalence may be underestimated.…”
Section: Discussionsupporting
confidence: 90%
“…The frequency of CMT patients with the MPZ mutations was determined to be 3.2% in the total independent patients and 4.7% in the patients negative for PMP22 duplication (Table 3). These frequencies were similar with those of the China (3.3% and 6.4%) (Hsu et al, 2019) and Britain (3.1% and 5.1%) (Murphy et al, 2012), but were relatively lower than those of most other examined countries.…”
Section: Resultssupporting
confidence: 83%
“…The frequencies of CMT patients with MPZ mutations are different depending on the ethnic groups. The frequency of CMT patients with the MPZ mutations from the total Korean cases was similar with Chinese (3.3%), British (3.1%), and Russian patients (3.5%) (Hsu et al, 2019; Mersiyanova et al, 2000; Murphy et al, 2012). However, the Korean frequency was somewhat lower than those in most of the other examined countries: from 4.0% in Austrians to 6.0% in Norwegians (Fridman et al, 2015; Gess et al, 2013; Manganelli et al, 2014; Milley et al, 2018; Miltenberger‐Miltenyi et al, 2009; Østern et al, 2013; Silander et al, 1998; Sivera et al, 2013; Yoshimura et al, 2019).…”
Section: Discussionsupporting
confidence: 54%
“…De novo MFN2 mutations are regularly found in patients with a classical CMT2 phenotype ( Østern et al, 2013 ), and some MFN2 mutations have also been reported as de novo in several patients ( Züchner et al, 2004 ; Chung et al, 2006 ; Verhoeven et al, 2006 ; Cho et al, 2007 ). The early onset of the proband, at 7 years old, is in line with data reporting that mutations in MPZ , MFN2 , or NEFL are the most frequent disease causes of patients with infantile-onset CMT ( Hsu et al, 2019 ).…”
Section: Discussionsupporting
confidence: 86%